Priorities in Sustainable Management After Settlement Arrangement in The Coastal Area of Tegalsari Village - Haidar, Noval Amani; Yuliastuti, Nany (Jurnal Riset Perencanaan Wilayah dan Kota, 2025)
Abstract. In 2015, the United Nations formulated 17 Sustainable Development Goals (SDGs) to address global issues, including Goal 11: Sustainable Cities and Communities. Slum areas, especially in coastal regions, are a key concern. Tegalsari Village in Tegal City was designated as a slum area in the 2014 Slum Decree by the Mayor of Tegal. In response, the Ministry of Public Works and Housing (PUPR) implemented a settlement improvement program, completed in 2019. This study aims to analyze the priority of coastal area management following the settlement arrangement in Tegalsari. A quantitative approach using the Importance Performance Analysis (IPA) method was employed. Results show the level of importance-performance alignment as follows: coastal area structuring (95%), spatial planning (92%), slum area sustainability (58%), area management (49%), and environmental quality (92%). Based on the Cartesian diagram, coastal area management and slum area sustainability fall into the top priority quadrant (1), while coastal structuring is in the maintain achievement quadrant (2). Spatial planning and environmental quality are placed in the excessive quadrant (4). Effective management of the Tegalsari coastal area requires collaboration between the government and local communities to ensure the sustainability of the improvements made.